Staff Guidance Note on Debt Limits in Fund-Supported Programs. (Policy Papers; Policy Paper, 2009)
In August 2009, the Executive Board approved new guidelines on external debt limits in Fund-supported programs. Debt limits seek to prevent the build-up of unsustainable debts, while allowing for adequate external financing. The new framework moves away from a single design for debt limits (or, to use the usual terminology, concessionality requirements) towards a more flexible approach.